Application of Selected Biomaterials and Stem Cells in the Regeneration of Hard Dental Tissue in Paediatric Dentistry—Based on the Current Literature - Alina Wrzyszcz-Kowalczyk; Maciej Dobrzynski; Iwona Grzesiak-Gasek; Wojciech Zakrzewski; Monika Mysiak-Debska; Patrycja Nowak; Malgorzata Zimolag; Rafal J. Wiglusz (Nanomaterials, 2021)
Currently, the development of the use of biomaterials and their application in medicine is causing rapid changes in the fields of regenerative dentistry. Each year, new research studies allow for the discovery of additional possibilities of dental tissue restoration. The structure and functions of teeth are complex. They consist of several diverse tissues that need to act together to ensure the tooth’s function and durability. The integrity of a tooth’s enamel, dentin, cementum, and pulp tissue allows for successful mastication. Biomaterials that are needed in dentistry must withstand excessive loading forces, be biocompatible with the hosts’ tissues, and stable in the oral cavity environment. Moreover, each tooth’s tissue, as well as aesthetic qualities in most cases, should closely resemble the natural dental tissues. This is why tissue regeneration in dentistry is such a challenge. This scientific research focuses on paediatric dentistry, its classification of caries, and the use of biomaterials in rebuilding hard dental tissues. There are several methods described in the study, including classical conservative methods such as caries infiltration or stainless-steel crowns. Several clinical cases are present, allowing a reader to better understand the described methods. Although the biomaterials mentioned in this work are artificial, there is currently ongoing research regarding clinical stem cell applications, which have a high potential for becoming one of the most common techniques of lost dental-tissue regeneration in the near future. The current state of stem cell development is mentioned, as well as the various methods of its possible application in dentistry.